AI as the Philosophy of a Matrix Society. Educational Implications - Kobylarek, Aleksander; Birova, Jana (Journal of Education Culture and Society, 2026)
Rapid technological development requires us to continually expand our knowledge and acquire skills that will help us to not only function in society in general but also interpret messages and meanings correctly. Self-development helps us to distance ourselves from untruths, think independently, become informed citizens and easily distinguish truth from falsehood. Primarily, Artificial Intelligence (AI) was made to support humans, yet in their lives, it has come to play a different role. It takes thinking out of their hands, that is comfortable, but it also uses multiple, also unreliable sources. AI has become a discussion (and not only a discussion) but also a partner, a doctor, a lawyer, an oracle. Generative Artificial Intelligence (GenAI) is coming to be a fast ,but often also unreliable assistant and adapted to users’ preferences and views, provides users with information and materials. This user places too much trust in AI and becomes complacent, knowing that they do not have to make any effort to get what they want or need. Educators now face an extremely difficult task of restoring younger generations’ faith in the meaning of science, independence, honesty, and critical thinking. The task is made even more difficult by the fact that the highest offices are held by people who display crassness and a lack of elementary knowledge, thus showing that it’s not worth being an honest and hardworking person. Nevertheless, this rapid development and human laziness prove that the topic of AI should still be explored by scientists from different disciplines, and that countries should ensure that appropriate regulations are in place to guarantee the safety of users. Especially as its rapid development affects not only younger generations but also people of all ages and at all levels.